Korupsi di Balik Jeruji: Menguak Praktik Pungutan Liar di Lembaga Pemasyarakatan Sukamiskin - Iwan Ridwan Paturochman; Zahra Rahmatia; Nafisa Naila Husna; Rafli Riyantoni Putra (Kampus Akademik Publiser, 2026)
The presence of luxurious cells within correctional facilities signifies an abuse of power by unethical law enforcement officials. This reflects an inequality in law enforcement and the services provided. The disparity between correctional facilities equipped with luxurious cells and those lacking proper facilities highlights the gaps within the correctional system. This research adopts a juridical-normative approach, utilizing both statutory and conceptual methods. The findings indicate that the principle of equality in treatment and service within correctional facilities remains unfulfilled, as many individuals exploit their power to obtain luxurious cell accommodations by paying high prices to corrupt officials, thus making prison facilities resemble star-rated hotels.